Multi-step infrared macro-fingerprint features and lipid metabolism in HepG2 cells: Intervention of different sourced phospholipids - Yulong Zhao; Xutao Li; Guihong Luo; Ryosuke Matsuoka; Yimeng Zhao; Qingqing Jiang; Long Zhang; Wenzheng Shi; Xichang Wang; Mingyu Yin (Applied Food Research)
This study examined the efficacy of capelin roe phospholipids (CPL), egg yolk phospholipids (EPL), and soybean phospholipids (SPL) on lipid metabolism disorders induced by oleic acid in HepG2 cells. The results showed that OA led to an increase in intracellular triglycerides, cholesterol, malondialdehyde, carbohydrates, nucleic acids, -CH2-, ν(C=O)/νas (CH2+CH3), and a decrease in cellular protein content, from which CPL, EPL, and SPL significantly inhibited these effects (P < 0.05). It was revealed that CPL, EPL, and SPL treatments inhibited oxidative stress and lipid peroxidation in cells while safeguarding intracellular nucleic acid structures to maintain normal energy metabolic pathways, based on FT-IR spectroscopy and chemometric analysis. This study highlights the potential direction for further development of phospholipid extraction and the creation of phospholipid-based functionalized products.